Activation Of Idle Production Capacities In The Iraqi Economy (Al-Mansour Journal, 2022)
Due to the changes in Iraq after 2003 the resulting problems in (economic, social and security) lead up to the deterioration of production capacities and abnormality in physical, financial , human or oil and gas energies , so this paper diagnose what ways and mechanisms can be pursued at the present stage to reactivate idle production capacities in the Iraqi economy and exploiting them, commensurate with the goals of alternative development.